Fatigue of Steel Plates with Inclusions - Jaroniek, Mieczysław; Niezgodziński, Tadeusz (Lodz University of Technology. Faculty of Mechanical Engineering. Department Division of Dynamics., 2015)
Manufactured by the end of the 80s in the last century steel structures were made of steel which contain signi cant amounts of non-metallic inclusions. As a result of many years of intensive use of the structures made of steel, structural discontinuity material combine to form internal cracks called lamellar cracks. These cracks are formed in rolled sheets with non-metallic inclusions. Studies of lamellar cracks began in the 1960s, but there is still no satisfactory theory explaining their formation.
Keywords: fatigue test; girder crane; non-metallic inclusions; próba zmęczeniowa; żuraw dźwigowy; inkluzje niemetaliczne